2014
DOI: 10.1039/c4dt01974a
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of hexagonal GeO2particles with particle size and crystallinity controlled by peptides, silk and silk-peptide chimeras

Abstract: We demonstrate the use of silk based proteins to control the particle/crystallite size during GeO 2 formation, using a bio-mimetic approach at circumneutral pH and ambient temperature. Multicrystalline GeO 2 was prepared from germanium tetraethoxide (TEOG) in the presence of different silk-based proteins: Bombyx mori silk (native silk) and two chimeric proteins prepared by linking a germania binding peptide (Ge28: HATGTHGLSLSH) with Bombyx mori silk via chemical coupling at different peptide loadings (silk-Ge2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…The chitin spectrum shows bands characteristic of the α-chitin polymorph and corresponds to previously published data [50,51]. The triplet band, characteristic of the GeO 2 hexagonal phase, is clearly visible between 588 and 520 cm -1 and is attributed to the Ge-O-Ge υ4 vibrational mode [24,27,45,[52][53][54][55]. The low-frequency bands around 555 cm -1 are equivalent with the longitudinal optic (LO) bending mode observed in the Raman spectrum at ~589 cm -1 (Fig.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…The chitin spectrum shows bands characteristic of the α-chitin polymorph and corresponds to previously published data [50,51]. The triplet band, characteristic of the GeO 2 hexagonal phase, is clearly visible between 588 and 520 cm -1 and is attributed to the Ge-O-Ge υ4 vibrational mode [24,27,45,[52][53][54][55]. The low-frequency bands around 555 cm -1 are equivalent with the longitudinal optic (LO) bending mode observed in the Raman spectrum at ~589 cm -1 (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…It was reported that these organic materials incorporated into the mineral did not appear to affect the unit-cell dimensions. Moreover, the germania-binding peptide alone did not have any significant effect on reaction rate, yield, or the material's properties in comparison with the control reference [45].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…FTIR spectrum of pure Agar confirmed by in the wavelength range of 950 and 1200 cm -1 are considered as the 'finger print' region for carbohydrates as it allows the identification of major chemical groups in polysaccharides [25]. This region is dominated by ring vibrations overlapped with stretching vibrations of (C-OH) side groups and the (C-O-C) glycosidic bond vibration.…”
Section: Ft-ir Studymentioning
confidence: 99%